PENGARUH PEMBANGUNAN FISIK DESA TERHADAP TINGKAT KEMISKINAN DI 21 DESA DI KECAMATAN JANGKA KABUPATEN BIREUEN - Ernita Ernita; Cut Putri Mellita Sari (LPPM Universitas Malikussaleh – Indonesia, 2019)
The study aimed to effect the amount of funding, village building on the level of poverty in the Jangka Subdistrict Bireuen District. The data used the secondary data derived from a. sub-district office The methodology used is. Quantitative Data analyzed by the method of multiple regression. The result showed that the total budget will not affect the level of poverty that hypothesis advanced by rejected the number of buildings will not affect the level of poverty that hypothesis advanced by the rejected.